Factors affecting the component community structure of haemoparasites in bank voles (Clethrionomys glareolus) from the Mazury Lake District region of Poland - Bajer, Anna; Pawelczyk, Agnieszka; Behnke, Jerzy M.; Gilbert, Francis; Sinski, Edward (Cambridge University Press, 2001)
The prevalence and abundance of infections with haemoparasites were studied over a 3 year period in Clethrionomys glareolus (bank vole, n=420) sampled from forests in the NE of Poland. Total species richness was 5 (Prevalence=Haemobartonella sp. 63.1%, Bartonella grahamii 27.4%, Hepatozoon erhardovae 31.4%, Trypanosoma evotomys 15% and Babesia microti 1.0%) with 81.9% of the voles carrying at least 1 species and a mean infracommunity species richness of 1.4. Variation in species richness was determined primarily by season and year, and the interaction of these factors. The observed frequency distribution of infracommunity species richness did not differ from that predicted by a null model, suggesting that there were no marked associations between the species. Analyses of prevalence and abundance of infection with each species in turn, revealed that overall the principal causes of variation were temporal and seasonal and their interaction, intrinsic factors such as age and sex playing only a minor role. However, the relative importance of specific extrinsic, and rarely intrinsic, factors varied and was distinct for each of the species in the study. Prevalence data revealed 4 sets of 2-way associations between species, mostly varyingly dependent on combinations of intrinsic and extrinsic factors. Analysis of quantitative associations suggested 4 sets of positive 2-way interactions, 3 of which remained after controlling for the effect of extrinsic and intrinsic factors on the abundance of each species, but only one could be unequivocally accepted (Haemobartonella sp. +B. grahamii) after correction for multiple comparisons. These data are discussed in the context of the changing ecological profiles in this region of Eastern Europe and, in a wider context, in relation to current understanding of the factors which shape component community structures of haemoparasites in wild rodents.